Magnesium Makes Many Products Better - Dow Chemical Company (1950)
Black and white print advertisement for Dowmetal, a magnesium alloy manufactured and sold by the Dow Chemical Company. The advertisement highlights one use of Dowmetal, a dictation machine. In particular, the ad calls attention to the durability, lightness, and low manufacturing cost afforded to the dictation machine because it was constructed from Dowmetal. Includes three inset images showing a man lifting a magnesium dictating machine, the man speaking into the dictating machine, and the dictating machine disassembled. The Dowmetal logo, a hand holding a winged ingot of magnesium, is located in the bottom right of the advertisement. Found on page 91 of Time Magazine, April 3, 1950 issue.
Keywords: Advertising; Dow Chemical Company; Advertising, Industrial; Chemical Industry; Magnesium alloys; Mineral industries